Punishing for the Past (Sometimes): Judicial Perspectives on Criminal History Enhancements - Hester, Rhys (The prison journal, 2021)
Prior criminal record is routinely cited as one of the primary determinants of sentencing, and the common view is that prior record was a leading factor in non-guidelines jurisdictions going back decades. Yet, recent findings from a non-guidelines state failed to conform to this account. This study uses interviews with judges from a non-guidelines state to understand the role of prior record in sentencing in an unstructured sentencing state. This study also reexamines some of the early sentencing guidelines formation literature and finds some indications that pre-guidelines, prior record was not universally an instrumental predictor of sentence length.